Selective synthesis of zeolitic phillipsite and hibschite hydrogarnet from lignite ash employing calcium hydroxide under mild conditions - Rujiwatra A. (2014)
A selective synthesis of zeolitic material, phillipsite, employing calcium hydroxide under mild chemical conditions is reported. This is to provide a potential method in reducing the amount of the waste from lignite power plant and the addition of economical value to the material. The fly ash was first activated by calcination at high temperature, and then fused with calcium hydroxide. The water was then added to the solid mixture before curing under saturated water vapour at low temperature. The treatment of as-received fly ash with either calcium hydroxide or a mixture of calcium and sodium hydroxide following as-described preparative procedure of phillipsite, but without prior calcination was also conducted, and led to the formation of Hibschite hydrogarnet, which was also evidentially selective. The following parameters, i.e. type and amount of alkali reagent, the amount of added water, fusion temperature and reaction time were investigated. Powder X-ray diffraction was used to identify type of crystalline solid products, and scanning electron microscope was employed to follow the alteration of solid morphologies. X-ray fluorescence (XRF) was used to trace the chemical composition of the solids. The heavy metal cation removal abilities toward lead ion of the prepared phillipsites were also investigated. © 2005 Elsevier Ltd. All rights reserved.